A comparative study of mixture formation and combustion processes in a gasoline Wankel rotary engine with hydrogen port and direct injection enrichment. (15th July 2018) - Yang, Jinxin; Ji, Changwei; Wang, Shuofeng; Wang, Du; Ma, Zedong; Ma, Lili
Highlights: A CFD model of H2 -gasoline fueled rotary engine was established and validated. A low velocity zone was existed in the rear chamber under HDIE conditions. Combustion completeness in the rear region was improved by proper HDIE. HDIE significantly increased the in-cylinder pressure in comparison with HPIE. Higher CO and NOx emissions were obtained under HDIE conditions. Abstract: A CFD model of hydrogen-enriched gasoline Wankel rotary engine is established and validated. The mixture formation and combustion processes are investigated under both hydrogen port and direct injection enrichment conditions with different hydrogen addition levels. It was found that, under hydrogen port injection enrichment conditions, the peak in-cylinder pressure of 6% is 8.4% higher that of 3%. Meanwhile, under hydrogen direct injection enrichment conditions, the peak in-cylinder pressure of 3% hydrogen direct injection enrichment is 15.3% higher than that of 3% hydrogen port injection enrichment. It was also found that the mainstream field with same direction of rotor rotation is formed during the compression stroke and a vortex with high vorticity existed in the combustion chamber. With the effects of mainstream field and vortex, the hydrogen fills more than half volume of the entire combustion chamber under 4%, 5% and 6% HDIE conditions. At the same time, a local low velocity zone is formed around the vortex because the hydrogen direct injection flow slows down the dissipation of vortex. According to the analysis by PREMIX, the fastest flame speed is achieved at equivalence ratios around 1.4. The proper rich hydrogen region distribution is obtained under 4%, 5% and 6% hydrogen direct injection enrichment conditions. Both the enhanced flame propagation by proper equivalence ratio distribution and the reduced local mainstream flow velocity by vortex existence contribute to solving the unburned zone problem. Compared with 6% hydrogen port injection enrichment, the maximum value of in-cylinder pressure of 4%, 5% and 6% hydrogen direct injection enrichment is improved by 59.6%, 88.4% and 91.6%, respectively. However, carbon monoxide and nitrogen oxide emissions are increased obviously. As a relatively low carbon monoxide emission is obtained with 4% case under hydrogen direct injection enrichment conditions and the problem of unburned zone in the rear region of combustion chamber is solved. The hydrogen volume fraction of 4% with direct injection enrichment achieves the best engine performance in this study.